(The Study on The thermal Energy Consumption and Effisiency in Coconut Oil Processing Using HOID Technology) - Lukman Junaidi; A S Tariq; Yang Yang Setiawan; Dadang Supriatna (Warta Industri Hasil Pertanian, 1999)
The study on the thermal energy consumption and efficiency in coconut oil processing using HOID technology was conducted to evaluate the performance of the thermal energy efficient fumace. the preliminary comsubtion experimental conducted to examine the thermal capacity of the system, indicated that the system could be used to fry minimum of 2 tons coconut meat per 8 hours operation. The frying capacity of the furnace was influenced significanrtly by the ration of the fresh coconut meat to coconut oil and the amount of coconut oil that should be replaced. The higher the ration will result in the higher of the frying rate. The result of experiment showed that the maximum thermal efficiency of the fumace was around 70% this maximum efficiency could be achieved if the loss of the thermal energy from the system could be made minimally, espencially loss due to the sensible heat in the dry flue gas and loss due to the incomplete combustion of fuel resulting in carbon monoxide in the flue gas. The average thermal efficiency of the system was 54%.